Safety profile and efficacy of tacrolimus in the treatment of birdshot retinochoroiditis: a retrospective case series review. Issue 7 (19th October 2017) - Islam, Farrah; Westcott, Mark; Rees, Angela; Robson, Anthony George; Kapoor, Bharat; Holder, Graham; Pavesio, Carlos
Abstract : Aim: Evaluation of the use of tacrolimus in the treatment of birdshot retinochoroiditis (BRC) at a tertiary referral centre with the aim to describe its safety and efficacy. Methods: The medical records of 25 patients diagnosed with BRC at uveitis service, Moorfields Eye Hospital, and who had received tacrolimus treatment were retrospectively reviewed. The main outcome measures of the study were (1) safety of tacrolimus in terms of side effects and (2) efficacy, as measured both by control of inflammation and visual function assessed by Humphrey visual fields and electrophysiological testing over at least 6 months and then 1 year. Results: Tacrolimus was commenced in 25 patients (mean age 50.4±10.8 years) and was well tolerated in 21 patients (84%). It was necessary to stop the tacrolimus in four patients. No patient showed major changes in renal function: 3/21 patients (14.28%) showed slightly abnormal (less than 30%) function at the end of the first month of treatment; 1/21 (4.76%) patients at 3 months, but at the end of a 6-month treatment period only 1/21 patients (4.76%) showed minor abnormality in renal function. The mean daily prednisolone dose was 19.7 mg at the beginning of the study, which had fallen to 6.9 mg at the end (t=5.071, p=0.001). Visual acuity mostly remained stable. Visual fields improved over time (mean improvement in Humphrey mean deviation, right eye=1.8±2.4 dB, t=3.821, p=0.004; left eye=1.9±2.7,  dB, t=3.06, p=0.007). Electrophysiological function showed improvement in 10 patients, and in four patients an initial deterioration in function improved following tacrolimus dose adjustment. Conclusion: Tacrolimus has a good safety profile for long-term use in patients with BRC as a second-line agent enabling steroid sparing and visual function stabilisation or improvement.